Apocalyptic Apologetics and the Witness of the Church - Graham Tomlin (Religions, 2023)
The discipline of apologetics has always been somewhat controversial in Christian theology. In the early church, the Greek-speaking apologists were often opposed for their attempts to express the gospel in the terms of Greek thought. In more recent times, the critiques of Soren Kierkegaard and Karl Barth, that it is an attempt to appeal to foundations that have nothing to do with the gospel, have cast a shadow over the discipline in recent years. This paper seeks to take those critiques seriously, yet argues that the discipline of apologetics is vital for the ongoing witness of the Church. It offers a new vision of apologetics based on the theological Apocalyptic genre. Rather than attempt to prove the existence of God or the truth of the Christian faith by rational means, Apologetics can be reconceived as an essentially narrative or descriptive discipline. The Apocalyptic genre thinks of the gospel as the result and announcement of the good news as a radical incursion of God into human life and history in the Incarnation and Resurrection. Apocalyptic Apologetics thus becomes an attempt to describe the world of history, politics, relationships and art (in fact, everything created) as lit up by the light of the glory of God in the face of Jesus Christ. It becomes a wide-ranging and imaginative venture to redescribe the world in the light of the gospel. This approach re-establishes Apologetics as a crucial part of the Church’s witness while avoiding the critique that it smuggles in assumptions and foundations from outside the gospel itself.